2021
DOI: 10.1167/jov.21.8.23
|View full text |Cite
|
Sign up to set email alerts
|

Salient objects dominate the central fixation bias when orienting toward images

Abstract: Short-latency saccades are often biased toward salient objects or toward the center of images, for example, when inspecting photographs of natural scenes. Here, we measured the contribution of salient objects and central fixation bias to visual selection over time. Participants made saccades to images containing one salient object on a structured background and were instructed to either look at (i) the image center, (ii) the salient object, or (iii) at a cued position halfway in between the two. Results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
(118 reference statements)
2
3
0
Order By: Relevance
“…3, 4 and 5), which renders it more likely that this performance benefit is related to the distractor (which precedes the target by 187 ms) rather than the target. Our previous findings showed that biases induced by suddenly appearing salient distractors can be overcome 250-300 ms after distractor onset (Wolf & Lappe, 2020, 2021a, which is temporally consistent with the present performance saturation around 100-120 ms after target onset. Taken together, although we cannot ultimately distinguish whether reward aids target facilitation or whether it improves distractor suppression, our results are more consistent with the latter.…”
Section: Discussionsupporting
confidence: 91%
“…3, 4 and 5), which renders it more likely that this performance benefit is related to the distractor (which precedes the target by 187 ms) rather than the target. Our previous findings showed that biases induced by suddenly appearing salient distractors can be overcome 250-300 ms after distractor onset (Wolf & Lappe, 2020, 2021a, which is temporally consistent with the present performance saturation around 100-120 ms after target onset. Taken together, although we cannot ultimately distinguish whether reward aids target facilitation or whether it improves distractor suppression, our results are more consistent with the latter.…”
Section: Discussionsupporting
confidence: 91%
“…For the second saccade, participants had to decide between two alternative targets (the selection targets). Importantly, rather than introducing a foveal task and manipulating the difficulty of the foveal target ( Ludwig et al., 2014 ), we manipulated target semantics, because eye movement control and foveal inspection are known to depend on cognitive processing demands and whether there is ample or little to see ( Inhoff and Rayner, 1986 ; Kliegl et al., 2004 ; Einhäuser et al., 2020 ; Wolf & Lappe, 2021a , 2021b ). Therefore, our targets were either meaningful face stimuli or meaningless noise patches.…”
Section: Introductionmentioning
confidence: 99%
“…However, even though the initial fixation point was positioned in the center of the screen in the present study, it is unlikely that our results were shaped by a strategic preference towards the center of the image because there was no need to extract scene information but rather to make a single goal-directed eye movement to a prespecified target. More importantly, the present results basically show that the central selection bias already occurs for the earliest eye movements, well before the typical period in which possible strategic control can be expressed (see also Wolf & Lappe, 2021).…”
Section: Discussionsupporting
confidence: 77%